2023
DOI: 10.1007/s00429-023-02634-x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the neurobiological effects of theta-burst stimulation (TBS) as measured using functional magnetic resonance imaging (fMRI)

Abstract: Theta burst stimulation (TBS) is associated with the modulation of a range of clinical, cognitive, and behavioural outcomes, but specific neurobiological effects remain somewhat unclear. This systematic literature review investigated resting-state and task-based functional magnetic resonance imaging (fMRI) outcomes post-TBS in healthy human adults. Fifty studies that applied either continuous—or intermittent—(c/i) TBS, and adopted a pretest–posttest or sham-controlled design, were included. For resting-state o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 118 publications
0
6
0
Order By: Relevance
“…This type of state-dependent accumulated brain changes that may result from spaced and repeated stimulation is referred to as metaplasticity and is well-known in non-human models 102104 . Indeed, intermittent TBS – delivering repeated and spaced TBS trains (as in this study) –has been shown to produce neural changes that could reflect plasticity while continuous TBS (no spacing between trains) did not – an effect which could be NMDA-receptor dependent 14,68,109 . In other words, intermittent TBS could be more conducive to triggering plastic changes in the human brain.…”
Section: Discussionmentioning
confidence: 63%
“…This type of state-dependent accumulated brain changes that may result from spaced and repeated stimulation is referred to as metaplasticity and is well-known in non-human models 102104 . Indeed, intermittent TBS – delivering repeated and spaced TBS trains (as in this study) –has been shown to produce neural changes that could reflect plasticity while continuous TBS (no spacing between trains) did not – an effect which could be NMDA-receptor dependent 14,68,109 . In other words, intermittent TBS could be more conducive to triggering plastic changes in the human brain.…”
Section: Discussionmentioning
confidence: 63%
“…It is more probable that many of the positive effects of TBS are the result of the secondary activation of glial cells, although there is limited information regarding the response of glial cells to these neuromodulation techniques ( Cullen and Young, 2016 ), particularly in relation to iTBS-induced plasticity effects ( Cacace et al, 2017 ). Moreover, knowledge about how intracortical structures, cortico-subcortical functional connectivity, and brain volume changes are involved in the modulatory effects of rTMS and TBS is still limited ( Di Lazzaro and Rothwell, 2014 ; Peters et al, 2020 ; Jannati et al, 2023 ; Kirkovski et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, anodal tDCS increases neuronal excitability, producing long-term potentiation (LTP)-like effects, while cathodal tDCS induces long-term depression (LTD)-like effects ( Rroji et al, 2015 ; Kronberg et al, 2017 ). Additionally, continuous TBS (cTBS) induces LTD-like cortical plasticity, whereas intermittent TBS (iTBS) produces LTP-like effects ( Kirkovski et al, 2023 ). In this study, the tBES pattern combines both facilitation and inhibition waveforms from direct current and TBS.…”
Section: Methodsmentioning
confidence: 99%